2014
DOI: 10.1159/000358635
|View full text |Cite
|
Sign up to set email alerts
|

Serum-Free Media and the Immunoregulatory Properties of Mesenchymal Stem CellsIn VivoandIn Vitro

Abstract: Background: Mesenchymal stem cells are capable of self-renewal and multi-lineage differentiation. They are used extensively to treat several diseases. Traditionally, mesenchymal stem cells are cultured in serum-containing media, typically supplemented with fetal bovine serum (FBS). However, the variability of FBS is likely to skew experimental results. Although serum-free media used to expand mesenchymal stem cells has facilitated remarkable achievements, immunomodulation of these cells in under serum-free con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…The result suggests that direct contact between ASCs and PBMCs inhibits the secretion of IFN-g and TNFa. Wu et al [55] reported a similar phenomenon of reduced IFN-g and TNF-a secretion of CD4 + T cells after coculture with MSCs. In their study, T cells were activated for higher IFN-g and TNF-a secretion by PHA/IL-2 exposure, and reduced secretion of these factors was observed after coculture with MSCs.…”
Section: Discussionmentioning
confidence: 73%
“…The result suggests that direct contact between ASCs and PBMCs inhibits the secretion of IFN-g and TNFa. Wu et al [55] reported a similar phenomenon of reduced IFN-g and TNF-a secretion of CD4 + T cells after coculture with MSCs. In their study, T cells were activated for higher IFN-g and TNF-a secretion by PHA/IL-2 exposure, and reduced secretion of these factors was observed after coculture with MSCs.…”
Section: Discussionmentioning
confidence: 73%
“…Mesenchymal stem cells (MSCs) are undifferentiated and multipotent adult stem cells that are mainly collected from the bone marrow, adipose tissue, and umbilical cord blood . MSCs have been used in various experimental models of diseases . Initially, the reparative and regenerative effects of MSCs were determined by their ability to be engrafted into various injured tissues .…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are a population of self-renewing multipotent cells that have significant clinical potential in cellular therapies for tissue regeneration [4,5].…”
Section: Introductionmentioning
confidence: 99%